2008
DOI: 10.1186/1476-4598-7-68
|View full text |Cite
|
Sign up to set email alerts
|

Impact of BRAF, MLH1 on the incidence of microsatellite instability high colorectal cancer in populations based study

Abstract: We have identified an alternative pathway of tumorigenesis in sporadic colon cancer, involving microsatellite instability due to mismatched repair methylation, which may be driven by mutations in the BRAF gene (V600E). Colorectal cancer (CRC) is the most common cancer in the world, and African Americans show a higher incidence than other populations in the United States. We analyzed sporadic CRCs in Omani (of African origin, N = 61), Iranian (of Caucasian origin, N = 53) and African American (N = 95) patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
2
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 41 publications
(89 reference statements)
6
51
2
3
Order By: Relevance
“…En el presente trabajo, los tumores con mutaciones en BRAF se asociaron significativamente a MSI alta y localización en el colon derecho, lo cual es consistente con reportes previos 33,34 . Aun más, ha sido reportado que la mutación activante en BRAF fue encontrada entre 10-18% de pacientes con CC y que este porcentaje se incrementa a 27-45% en quienes presentan tumores MSI alta 35,36 , en concordancia nosotros observamos 9% de mutación en BRAF en nuestra población de estudio y que alcanza a 27% en aquellos con MSI alta.…”
Section: Discussionunclassified
“…En el presente trabajo, los tumores con mutaciones en BRAF se asociaron significativamente a MSI alta y localización en el colon derecho, lo cual es consistente con reportes previos 33,34 . Aun más, ha sido reportado que la mutación activante en BRAF fue encontrada entre 10-18% de pacientes con CC y que este porcentaje se incrementa a 27-45% en quienes presentan tumores MSI alta 35,36 , en concordancia nosotros observamos 9% de mutación en BRAF en nuestra población de estudio y que alcanza a 27% en aquellos con MSI alta.…”
Section: Discussionunclassified
“…The basic tests identify five markers (NR-21, BAT-26, BA T -25, NR-27 and NR-24) to devise the simplest diagnostic assay (9). Previous reports have shown significant diversity regarding the most common marker for microsatellite testing; BAT 25, BAT26 and NR21 have been reported in HNPCC and sporadic CRCs (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Table 1 shows the reports from Iran that studied the frequency of MMR genes in both hereditary and sporadic colorectal cancers.…”
Section: Microsatellite Instability (Msi)mentioning
confidence: 99%
“…Table 1 shows the reports from Iran that studied the frequency of MMR genes in both hereditary and sporadic colorectal cancers. As it shows, the frequency of MSI in patients with HNPCC has been 29% -62.5% (9-25), there are not so many studies about the frequency of MSI in sporadic CRC from Iran; however, the reported frequencies of MMR have been from 19.4% to 66.6% (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Microsatellite Instability (Msi)mentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of BRAF mutation in CRC patients differs among ethnic groups. Brim et al (28) analyzed BRAF mutation in CRC patients of different ethnic groups, African American, Omani and Iranian. Among these CRC patients, BRAF mutation was detected in 10% of the African Americans, 19% of the Omanis, and 2% of the Iranians.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%